Behaviour of engineered nanoparticles in a lab-scale flame and combustion chamber. (August 2017) - Baumann, W.; Teuscher, N.; Hauser, M.; Gehrmann, J.; Paur, H.-R.; Stapf, D.
Abstract: Nanostructured materials are widely used to improve the properties of consumer products such as tires, cosmetics, light weight equipment etc. Due to their complex composition these products are hardly recycled and thermal treatment is preferred. In this study we investigated the thermal stability and material balance of nanostructured metal oxides in flames, in a pilot scale combustion plant and an industrial hazardous waste incinerator. We studied the size distribution of nanostructured metal oxides (CeO2, TiO2, SiO2 ) in a flame reactor and in a heated reaction tube. In the premixed ethylene/air flame, nano-structured CeO2 partly evaporates forming a new particle mode. This is probably due to chemical reactions in the flame. In addition sintering of agglomerates takes place in the flame. In the electrically heated reaction tube however only sintering of the agglomerated nanomaterials is observed. Ceria has a low background in waste incinerators and is therefore a suitable tracer for investigating the fate of nanostructured materials. Low concentrations of Ceria were introduced by a two-phase nozzle into the post-combustion zone of a waste incinerator. By the incineration of coal dust in a burning chamber the Ceria nanoparticles are mainly found in the size range of the fly ash (1 – 10 µm) because of agglomeration. With gas as a fuel less agglomeration was observed and the Ceria nanoparticles were in the particle size range below 1 µm.